CONSTITUTIONAL AND LEGAL FRAMEWORKS FOR LOCAL SELF-GOVERNANCE: A COMPARATIVE STUDY OF SOUTH ASIAN DEMOCRACIES (Lex localis - Journal of Local Self-Government, 2025)
The article is a critical study of the constitutional and legislative frameworks of local self-government in the five South Asian democracies that include India, Pakistan, Bangladesh, Nepal, and Sri Lanka. The works assumed a comparative constitutional methodology in order to study the level of local government autonomy, fiscal decentralisation, democratic participation, and accountability. The law was analysed qualitatively through a doctrinal analysis of the constitutional documents, national and local legislations, judicial interpretation, as well as the policy reports. The results are that there exist vast inequities: India and Nepal have developed strong structures of local autonomy and fiscal decentralisation systems, and Pakistan, Bangladesh, and Sri Lanka are struggling with political centralization, unbalanced legal frameworks, and underperforming implementation. India and Nepal have well-developed systems of direct election of local bodies, which have increased engagement in democracy, and Sri Lanka has a more top-down system of governance, which discourages participation by people. Other than this, India and Nepal have adequate accountability institutions, such as, though not limited to, the judiciary, ombudsman institutions, and Pakistan, Bangladesh, and Sri Lanka are struggling to be transparent and accountable at their local governance levels. The paper also determines the need to reinforce the policies of decentralisation, fiscal autonomy, and enhanced accountability institutions as a way of enhancing local government and democratic participation in South Asia. The lessons learned can then be used to provide some useful recommendations on policy making and subsequent academic studies on the problem of decentralisation and governance in the region.